European integration and the gains from trade - Gianmarco I. P. Ottaviano (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
This chapter discusses whether and how 'new quantitative trade models' (NQTMs) can be fruitfully applied to quantify the welfare effects of trade liberalization, thus shedding light on the trade-related effects of further European integration. On the one hand, it argues that NQTMs have indeed the potential of being used to supplement traditional 'computable general equilibrium' (CGE) analysis thanks to their tight connection between theory and data, appealing micro-theoretical foundations, and enhanced attention to the estimation of structural parameters. On the other hand, further work is still needed in order to fully exploit such potential.
Keywords: F10; F15; F17; 330; Gains from trade; European integration; Quantitative trade models; Gravity equations; Structural estimation